KAJIAN ETNOBOTANI TUMBUHAN OBAT MASYARAKAT DESA MUARA PAGATAN KECAMATAN KUSAN HILIR KABUPATEN TANAH BUMBU - Muhammad Rifandi; Rosidah Rosidah; Yuniarti Yuniarti (Jurnal Sylva Scienteae, 2020)
Since ancient times, humans have relied heavily on the surrounding environment to meet their needs, for example to eat, shelter, clothing, medicine, fertilizer, perfume, beauty and others. The study of the relationship between humans and plants in their utilization activities has traditionally been called ethnobotany. This study aims to identify what types and parts of plants can be used and known as drugs by the community. And describe how to process or mix medicinal plants used by the community. . The approach method used in this study is collecting data about plants as medicine obtained from the community by using semi-structured interview techniques and questionnaires. Resource persons were selected using purposive sampling technique. Based on the results of the preliminary study taking into account the level of knowledge, skills and application or utilization of HHBK in the area. There are 18 types of medicinal plants that are often used by the people of Muara Pagatan Village as medicine to treat diseases such as diarrhea, ulcers, high blood pressure, parts of the plant that are most widely used by the people of Muara Pagatan Village as a medicine, namely leaf parts with 55,56 % compared to other plant parts and the method of processing that is often done to be used as medicine by the community of Muara Pagatan Village by boiling with a percentage of 66.67%, while for the method of use that is most often used by the community is by drinking with a percentage of 66.67%..Keyword: ethnobotany; muara pagatan; medicinal plants